Effectiveness of Gac Aril Extract to Stickiness, Retrogradation and Staling of Glutinous Rice Cake - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2020)
Gac fruit (Momordica cochinchinensis Spreng) is a popular fruit in rural area of Vietnam. Its aril contain high amount of β-carotene, lycopene, α-tocopherol and fatty acid. Its bright red color attracts consumers besides phytochemical constituents. It is very important to utilize these valuable constituents in Gac aril for multiple food processing applications. Glutinous rice cake is a kind of folk cake, very rustic, was present very early in the cuisine of Vietnam, also the specialty cakes of the local countryside, quite familiar and impressed in the hearts of people, products with aromatic fatty flavor, tasty, sweet flowing with delicate. Nowadays consumers require glutinous rice cake with superior appearance, texture, taste and flavor while stabilizing its nutritional value. Therefore in this present research, we examined the supplementation of Gac aril extract in different concentrations (2.0, 3.0, 4.0, 5.0%, 6.0%) to the physico-chemical, sensory and shelf-life of the glutinous rice cake. Our results showed that 5.0% Gac aril extract was adequate to supplement into glutinous rice cake making to extend its shelf-life for 5 days. Consumers have more chance to enjoy glutinous rice cake in good appearance and high functional properties.Keywords: Gac aril extract, Glutinous rice cake, Supplementation, Physico-chemical, sensory, Shelf-life.